Prácticas inclusivas para la población en condición de discapacidad en servicios sociales (2026)
Within the framework of responding to the needs of individuals with disabilities in Colombia, there is a growing demand for the implementation of inclusive practices that ensure access to and quality of social services. This study focuses on three key variables—attitude, social norms, and perceived self-efficacy among professionals—that influence the intention of team members at the Colombian Institute of Family Welfare (ICBF) to adopt inclusive practices. Through a content analysis of semi-structured interviews with seven professionals from the ICBF, the study explores how these variables impact the implementation of strategies benefiting individuals with disabilities. The results reveal that while a favorable social norm and positive attitudes toward inclusion training exist, numerous professionals encounter low perceived self efficacy and negative attitudes, often attributed to insufficient specialized training and limited resources. In conclusion, the study highlights the importance of enhancing training programs and resource availability for ICBF professionals to foster inclusive practices that ensure the well being and rights of individuals with disabilities in Colombia